APPLICATION OF ACCOUNTING RULES AND STANDARDS TO FINANCIAL STATEMENTS. - Greer, Howard C. (The Accounting Review, 1938)
Abstract The Executive Committee of the American Accounting Association has presented a tentative statement of principles, which deals with these questionable points. Everything that appears in this list could be definitely disposed of by every accountant if those principles, or rules, or standards, or conventions, or whatever you want to call them, were universally observed. But, if the universal observance of those particular rules and conventions and standards is not most desirable, then it behaves the accounting profession and those who are teachers and research workers in this field to decide what rules should apply. If qualifications and exceptions are necessary in connection with them, then the problem is to state them. It is a difficult, complicated task, but it is not impossible. Only our diffidence, our preoccupation with other matters, a certain degree of inertia in tackling these things, prevents our getting this job done in some satisfactory fashion. in some satisfactory fashion.